Kliinilise auditi „Naha melanoomi diagnostika ja ravi 2012. aastal esmashaigestunud patsientidel” kokkuvõte - Padrik, Peeter; Soplepmann, Jaan; Hussar, Karin; Teras, Jüri; Teras, Marina; Putnik, Kadri; Ojamaa, Kristiina; Adamson, Aidi; Saretok, Mikk (Eesti Arst, 2014)
Eesti Arst 2014; 93(8):445–447